The triumph of sociobiology - Alcock, John (Oxford University Press, 2001)
In The Triumph of Sociobiology, John Alcock reviews the controversy that has surrounded evolutionary studies of human social behavior following the 1975 publication of E.O. Wilson's classic, Sociobiology, The New Synthesis. Denounced vehemently as an "ideology" that has justified social evils and inequalities, sociobiology has survived the assault. Twenty-five years after the field was named by Wilson, the approach he championed has successfully demonstrated its value in the study of animal behavior, including the behavior of our own species. Yet, misconceptions remain--to our disadvantage